Effect of Ocimum tenuiflorum Leaf Extract against Infective Endocarditis - S Meghashri; JB Chauhan; AA Syed; F Zameer (International Journal of Phytomedicine, 2011)
The ever increasing resistance of pathogens to antibiotics as well as the undesirable side effects of certain antimicrobial agents has necessitated the discovery of novel natural products. The ethanolic extract of O. tenuiflorum was investigated against S. aureus isolate which is a major pathogen causing infective endocarditis. The total phenolic content in O. tenuiflorum was found to be 1289 μg gallic acid equivalent/g and HPLC profile revealed the presence of catechin, Caffeic acid and p-coumaric acid. The antibacterial profile of O. tenuiflorum against S. aureus isolate from infective endocarditis patients exhibited significant inhibition at the MIC of 50 μg/ml and the standard antibiotic Vancomycin showed inhibition at 40 ng/ml. Percent inhibition of viable growth was found to be >95% and the scanning electron micrographs (SEM) revealed the disruption of the membrane of S. aureus treated with O. tenuiflorum extract. The antimicrobial activity correlates with phenolic content of the extract. These results demonstrate the potency of O. tenuiflorum, could serve as a new source of antimicrobials with potential applications and related health benefits.